PO158 Sarcoidosis following alemtuzumab treatment for multiple sclerosis. (1st December 2017) - Willis, MD; May, K; Hope-Gill, B; Flood-Page, P; Jeffrey, D; Joseph, F; Robertson, NP
Abstract : Alemtuzumab, a licensed treatment for relapsing multiple sclerosis (MS) has proven efficacy in reducing relapse rates and improving disability outcomes. However, despite these beneficial effects, approximately 50% of patients develop secondary autoimmune disease (AID). The constellation of AIDs reported thus far encompasses Th2, B cell/antibody-driven pathologies including thyroid autoimmunity, idiopathic thrombocytopenic purpura and Goodpasture's syndrome. In contrast to this, we present two patients with MS treated with alemtuzumab whom subsequently developed systemic sarcoidosis, a Th1 mediated disease. The first case presented with chest pain and shortness of breath 8 years after the initial infusion of alemtuzumab with computed tomography (CT) of the thorax demonstrating widespread lymphadenopathy and peri-bronchovascular nodularity. Biopsy of a cervical lymph node demonstrated non-caseating granulomas with the changes considered consistent with sarcoidosis. Four years after initial infusion, the second case was found to have incidental right-sided hilar lymphadenopathy following routine Xray with CT demonstrating widespread lymphadenopathy. Subsequent sub-carinal lymph node core biopsy demonstrated granulomatous inflammation in association with a raised serum ACE and a diagnosis of sarcoidosis was made. To our knowledge, these are the first reported cases of Th1-cell mediated secondary autoimmunity following alemtuzumab for MS and we speculate on the possible immunological mechanisms to account for this.